PENGEMBANGAN KOMPETENSI AKUNTANSI MELALUI PELATIHAN JURNAL PENUTUP UNTUK SISWA/I SMK TRI RATNA - Fung Jin Tjhai; Christina, Silvy; Ricky A. Mulyana (Bajang Institute, 2025)
In response to the rapid development of globalization, digitalization, and industrialization, significant transformations have occured in various fields, including accounting. The accounting recording system has shifted from a traditional approach to a technology-based approach. However, understanding the basic concepts of accounting, such as preparing closing journals and post-closing trial balance, remains a challenge for students - particularly at SMK Tri Ratna. In response to this, the Trisakti School of Management organized a training session aimed at helping 10th-grade students master the process of creating closing journals and preparing a post-closing trial balance for a trading company. This session took place on August 21, 2024, and was enthusiastically attended by 19 students. The training consisted of a combination of theoretical discussions, practical exercises, and evaluations through post-tests and questionnaires. The results of the post-event questionnaire indicated that the session effectively enhanced students' understanding of the material, as reflected in the high evaluation scores given by the participants. This initiative is expected to be held regularly, with the aim of deepening students' knowledge of accounting from an early age, ultimately equipping them with essential skills for their future careers.